2021
DOI: 10.1002/jcla.24179
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of periostin in lung cancer‐related malignant pleural effusion

Abstract: Background Periostin (POSTN) is an extracellular matrix protein that is overexpressed in lung cancer and is considered an effective diagnostic and prognostic biomarker for lung cancer. The purpose of this study was to investigate the diagnostic performance of POSTN and to further evaluate the diagnostic value of POSTN combined with carcinoembryonic antigen (CEA) and cancer ratio [CR: serum lactate dehydrogenase (LDH)/pleural effusion adenosine deaminase (PE ADA)] in lung cancer‐related malignant PE (MPE). Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Lung cancer is one of the most common malignant cancers worldwide, and its early diagnosis is very important for the prognosis of patients. [21] At present, the emerging molecular diagnostic methods of lung cancer have attracted wide attention due to their sensitivity and objectivity. [22] Studies have shown that SHOX2 and RASSF1A aberrant methylation detection has an important link with cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignant cancers worldwide, and its early diagnosis is very important for the prognosis of patients. [21] At present, the emerging molecular diagnostic methods of lung cancer have attracted wide attention due to their sensitivity and objectivity. [22] Studies have shown that SHOX2 and RASSF1A aberrant methylation detection has an important link with cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%